The Influence of Traditional Engklek Games on Improving Interrogative Sentence Writing Skills in Elementary School Students: An Experimental Study - Moh Rif'an Maulana; Tri Sukitman; Yeni Puji Astuti (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: Elementary education in Indonesia continues to face significant challenges in developing students’ writing skills, particularly in constructing correct interrogative sentences. To address this issue, this study explores the use of traditional games, specifically the engklek game, as an innovative pedagogical tool to enhance interrogative writing abilities among elementary school students. Methodology: This research employed a quasi-experimental design with a quantitative approach, involving 60 fifth-grade students divided into an experimental group (using the engklek game) and a control group (using conventional instructional methods). Data were gathered through pre-test and post-test assessments consisting of 20 multiple-choice questions targeting interrogative writing skills. Statistical analysis was conducted to measure learning gains and treatment effects. Main Findings: The results demonstrated that students in the experimental group achieved a significantly higher post-test average score (19.33) compared to the control group (11.45). The N-Gain score analysis revealed a moderate improvement (0.72) for the experimental group, while the control group exhibited only low improvement (0.35). These findings affirm that integrating the engklek game can meaningfully boost students' ability to construct interrogative sentences. Novelty/Originality of this Study: This study introduces a novel intersection between traditional cultural practices and modern pedagogical needs by demonstrating how the engklek game typically associated with physical activity can be repurposed as an effective literacy development tool. It offers new insights into culturally responsive teaching strategies, advocating for the systematic integration of indigenous games into formal curricula to enhance engagement, contextualize learning, and improve academic outcomes in foundational language skills.